Implications of labour risks perceived by nurses in value granted to care and the caretaker in the Internal Medicine Service Hospital Nacional Guillermo Almenara Irigoyen, Lima, 2016 - Mercedes Zapata Silva, Irene (2019)
Objective: To describe and analyze the perception of occupational hazards of nurses in the care process and itsimplications. Methods: a qualitative study was by etnometodología conducted in a sample of eleven nurses ofinternal medicine defined by saturation criterion. The instruments were semi-structured interviews and participantobservation. Results: Three ethnocategories was obtained, you look for thematic analysis: (1) Risk of infectiousdiseases and accidental punctures; overuse injuries; emotional involvement and stress; suffer aggression and beingimmersed in lawsuits. (2) The implications nurse were deficits in physical and emotional health and (3) the institutionis urgent to overcome the limitations: furniture and obsolete equipment, the value of care and who cares for apreventive culture. Conclusions: the perception of occupational risks and their implications, revealed in multiplerisky situations, being emerging risk being attacked and being immersed in lawsuits by the new configuration ofuser-citizen. Authorities must manage, creating healthy conditions for the realization of care and nursing care; morecritical stance and attitude of transforming existing labor conditions by nurses is required, according to the existinglegislation on health and safety at work; strategy to mitigate and solve one of the greatest discords: work stress.Nurses recognize that care is “work necessary for humans, implying very high wear quotas”